Parecoxib does not suppress thromboxane synthesis in newborn piglets with group B streptococcal sepsis - Nögel, Stephanie; Chada, Martin; Schmidt, Ariana; Bosselmann, Stephan; Kandler, Michael; Schweer, Horst; Watzer, Bernhard; Schneider, Holm; Gessner, André; Rascher, Wolfgang (Prostaglandins & Other Lipid Mediators, 2009)
Group B streptococci (GBS) cause fatal sepsis in newborns. Strong activation of thromboxane synthesis is assumed to correlate with severe pulmonary hypertension. In this study we compared the impact of indomethacin versus parecoxib on hemodynamics and outcome and investigated the pharmacological effects on thromboxane synthesis and EP-3 receptor gene expression. Whereas both parecoxib and indometacin reduced expression of thromboxane synthase and EP-3 receptor in infected lung tissue, parecoxib did not suppress urine levels of thromboxane like indometacin. We presume that COX-2 inhibition in GBS sepsis is associated with enhanced thrombogenicity. © 2009 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Group b streptococcal sepsis; Parecoxib; Thromboxane